Pengaruh Biaya Produksi Dan Laba Yang Diinginkan Terhadap Harga Jual Pada UMKM Dua Putri Beton - Dewi Intan Sari; Mitha Otik Wiraswati (Fakultas Ekonomi Universitas Panca Marga, 2020)
Business actors must determine the selling price of a product appropriately in order to provide benefits for their business. The purpose of this research is to find out the desired production costs and profits whether they have an influence on the selling price at UMKM Dua Putri Beton Wringinom Gresik with a descriptive analysis method with a quantitative approach based on primary data. Observation, documentation, and interviews are data collection techniques from this research. The results showed that there was a significant influence on production costs and desired profit on the selling price of concrete buis products at UMKM Dua Putri Beton Wringinom Gresik, as evidenced by the results of the SPSS 21 for windows test, it is known that production costs have a positive effect on selling prices because production costs determine the high or low level of the selling price specified in a product. The desired profit has a positive effect on the selling price because if you want a large profit, the selling price for each set product must be high. The coefficient of determination (r2) is 98.6%. The calculation of production costs and the desired profit has a simultaneous effect on the selling price of concrete buis products at UMKM Dua Putri Beton Wringinom Gresik. Keywords: Production Costs, Desired Profits, Selling Prices